Determination of brick provenance and technology using analytical techniques from the physical sciences - PAVIA, SARA (Blackwell, 2006)
This work applies established analytical techniques of physical sciences to Irish brick in order to gather evidence of ceramic technologies, provenance and sources of raw materials. Petrographic microscopy, X-ray diffractometry and scanning electron microscopy with an energy dispersive X-ray diffraction attachment were used to study the brick of Rathfarham Castle, Dublin, built c.1618, where clay brick was introduced in 1771. Local clay was fired in the laboratory and analysed in a similar manner. The petrography of the pointing mortar was studied in order to gather evidence of ceramic provenance. This paper concludes that the brick was hand- moulded with a silica-based, predominantly non-calcareous clay of glacial origin gathered locally, including fluxes and a high percentage of non-plastic material. The mineralogy and petrography of the brick together with the presence of pebbles and a coarse-matrix suggest that the raw clay was probably gathered from a glacial deposit. The presence of abundant pebbles and colour inhomogeneities suggests a lack of processing of the raw clay. The brick was probably fired in clamps at top firing temperatures of 750 to above 900 ?C. Transformation of limestone temper involving breakdown of calcite and generation of calcium silicates, new-formation of plagioclase, high-temperature quartz, hematite and spinel were evidenced. The presence of spinel in `hot spots? indicates that fuel was added to the raw clay in order to assist firing.
PUBLISHED
Keywords: brick technology; petrographic microscopy; mortar; SEM/EDX; XRD; Dublin; provenance